Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/ma300945k
|View full text |Cite
|
Sign up to set email alerts
|

Structure Formation in Low-Bandgap Polymer:Fullerene Solar Cell Blends in the Course of Solvent Evaporation

Abstract: The drying process of the bulk heterojunction (BHJ) layer has a strong impact on the solar cell performance for the well-investigated material system P3HT:PC 61 BM. For higher performing low-bandgap polymers and C 71 fullerene derivatives, no comprehensive studies of the BHJ structure evolution during film drying are available. In this work we investigate the structure formation of the low-bandgap polymer poly{[4,40-bis(2-ethylhexyl)dithieno(3,2-b;20,30-d)silole]-2,6-diyl-alt-(2,1,3-benzothidiazole)-4,7-diyl} … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
(73 reference statements)
1
23
0
Order By: Relevance
“…Initially, the dominant source of X-ray scatter (at Q = 1.15 and 1.82 Å −1 ) is from DCB solvent molecules. [ 22,32 ] As the solvent content reduces, the relative intensity of these diffuse solvent scattering rings decreases. At approximately 230 s into the fi lm drying process (corresponding to the point where the relative solid content of the fi lm has substantially increased), X-ray scatter from PCDTBT and PC 70 BM begins to dominate (see Figure 3 (c)).…”
Section: Drying Dynamics Of Pcdtbt:pc 70 Bmmentioning
confidence: 99%
“…Initially, the dominant source of X-ray scatter (at Q = 1.15 and 1.82 Å −1 ) is from DCB solvent molecules. [ 22,32 ] As the solvent content reduces, the relative intensity of these diffuse solvent scattering rings decreases. At approximately 230 s into the fi lm drying process (corresponding to the point where the relative solid content of the fi lm has substantially increased), X-ray scatter from PCDTBT and PC 70 BM begins to dominate (see Figure 3 (c)).…”
Section: Drying Dynamics Of Pcdtbt:pc 70 Bmmentioning
confidence: 99%
“…This interpretation of the polymer orientation from SE experiments fits well to the time-resolved x-ray analysis that we published earlier, where we found that PSBTBT nucleation takes place in defined orientation at an interface, while randomly oriented aggregates form in the bulk during solvent evaporation. 29 As the degree of PSBTBT∶PC 71 BM anisotropy is similar to the anisotropy of neat PSBTBT, the polymer orientation remains mostly unaffected upon blending with PC 71 BM.…”
Section: Polymersmentioning
confidence: 91%
“…The blend ratios were chosen according to optimized process protocols. 27,29 SE data of the neat polymer films and the blend films were recorded between 250 and 1,700 nm at different angles of incidence α between 30 and 80 deg in 5 deg steps. Datasets were analyzed over the entire spectral range.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations